Investigation of effects of aerobic exercise on pregnancy and its circumstances - A.M Memari; T Ramim; M Amini; A Mehran; A Ajorloo; P Shakibaei (Tehran University of Medical Sciences, 2006)
Background & Aim: Many of the studies show benefit effects of exercise on mother and fetus during pregnancy. The aims of this research include of assessment of effects aerobic exercise on three factors: pregnancy age, birth weight and apgar score. Methods & Materials: During an experimental study, 80 pregnant women who referred to prenatal clinics in zone of 17 of Tehran were selected and divided in two equal groups. Inclusion criteria included, 18-35 years old, 18 weeks of pregnancy, second gravidity, without history of medical illness and exercise before pregnancy. In case group samples were under 15-30 minutes aerobic exercises with 50-70% Vo2 max 3 days a week for 8 weeks. Data were analyzed by SPSS version 10.5 soft ware and t test and 2 were used for statistical analysis. Results: Total 80 pregnant women enrolled in two groups. There were no statistically significant differences between cases and control in demographic factors. The most of cases were in 40 weeks group and more and the most of control were in 38-40 weeks however, there are no statistically significant differences between cases and control. The most of infants of cases and control mothers (60% and 70%, respectively) were in 2500g-3500g group but no statistically significant differences between cases and control. There are statistically significant differences between cases and control in 5 minute apgar score (p=0.01). Conclusion: In overall, the results show aerobic exercise improve 5 minute apgar score, but do not show significant effects on pregnancy age and birth weight.